Review of stability and stabilization for impulsive delayed systems - Xueyan Yang; Xiaodi Li; Qiang Xi; Peiyong Duan (Mathematical Biosciences and Engineering)
This paper reviews some recent works on impulsive delayed systems (IDSs). The prime focus is the fundamental results and recent progress in theory and applications. After reviewing the relative literatures, this paper provides a comprehensive and intuitive overview of IDSs. Five aspects of IDSs are surveyed including basic theory, stability analysis, impulsive control, impulsive perturbation, and delayed impulses. Then the research prospect is given, which provides a reference for further study of IDSs theory.